Activating Mutation (V617F) in the Tyrosine Kinase JAK2 is Absent in Locally-Confined or Castration-Resistant Prostate Cancer. (2010) - Gu, Lei; Zhu, Xian-Hua; Visakorpi, Tapio; Alanen, Kalle; Mirtti, Tuomas; Edmonston, Tina Bocker; Nevalainen, Marja T.
Abstract : Background: Transcription factor Stat5a/b is highly critical for the viability of human prostate cancer cells in vitro and for prostate tumor growth in vivo . Stat5 is constitutively active in clinical prostate cancers but not in the normal human prostate epithelium. Moreover, Stat5a/b activation in prostate cancer is associated with high histological grade of prostate cancer. However, the molecular mechanisms underlying constitutive activation of Stat5a/b in prostate cancer are unclear. The receptor-associated tyrosine kinase Jak2 is a known key activator of Stat5a/b in prostate cancer cells in response to ligand stimulation. Recently, a single gain-of-function point mutation of JAK2 was described in myeloproliferative diseases leading to constitutive Jak2 kinase activity, subsequent Stat5a/b activation and involvement of V617F Jak2 in the pathogenesis of myeloproliferative disorders. Materials and Methods: We determined whether JAK2 undergoes the V617F activating mutation during clinical progression of human prostate cancer using a highly sensitive assay (amplification refractory mutation system) and a unique material of fresh specimens from organ-confined or castration-resistant prostate cancers. Results: The JAK2 V617F mutation was not found in any of the normal or malignant prostate samples analyzed in this study. Conclusions: Future work should focus on determining the molecular mechanisms other than V617F mutation of Jak2 resulting in continuous Stat5 activation in clinical prostate cancers.